Preparation and Performance Analysis of CI Engine Run by Blends of Diesel and Biodiesel (Karanja Oil) - Ananth Vino, V. Jose; Patel, Ashish; Kumar, Arun; Kumar, Abhishek; Yadav, Ajay (International Journal of Psychosocial Rehabilitation, 2019)
Biodiesel is an alternative fuel to diesel and is described as a fatty acid methyl ester from vegetable oil or animal fats. The main objective of our project is to reduce the higher viscosity of Karanja oil by transesterification and to increase the performance and emission characteristics of diesel engines. By using the biodiesel from pun gam oil, the performance test of the biodiesel blend (B00, B10, B20) in 1500 rpm and a 5 bhp mechanically loaded CI engine is tested. By using different blends, we have identified the engine parameters such as brake thermal efficiency, specific fuel consumption, total fuel consumption, and brake power. In this, finally, we have determined which blend is better and which consumes less fuel. Biodiesel has the distinct advantages of being a renewable, biodegradable, & eco-friendly fuel. During the recent years, in the field of alternative fuels, especially in the area of biodiesel, research has been extensively carried out, and different samples of biodiesel have been prepared considering the scope, availability, and economics of various edible and non-edible oils. Biodiesel from Mahua, Linseed, Rice Bran, Waste Cooking Oil, Crude Palm, Castor, Jatropha, & Karanja has already been prepared and successfully tested in diesel engines & vehicles. Small capacity reactors of 5 & 10 liters of biodiesel were designed and developed also for experimental purposes. As per the Ministry of Rural Development, the National Mission on Biodiesel is proposed to be implemented in two phases. The first phase will involve a demonstration stage for the plantation of jatropha on four lakh hectares and associated research activities for establishing the commercial viability of the fuel. Phase two will involve self-sustaining expansion of the biodiesel program. The overall objective of the national mission is to promote the creation of national infrastructure for production of biodiesel through cultivation of the jatropha plant and processing of its oil.